2021
DOI: 10.3390/s21092903
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Spectra Analysis of Drawbar Pulls Generated by Special Driving Wheels Improving Tractive Performance

Abstract: Driving wheel operation is characterized by force interactions with the ground, manifested in the form of vibrations. Signals generated by driving wheels can be analyzed in the frequency spectrum of tractor drawbar pull. The paper presents the analysis of a drawbar pull signal generated by a tractor equipped with two types of special driving wheels and standard tires. Beside the evaluation of special driving wheels’ properties according to drawbar power, the frequency spectra of measured signals were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The effect of spike tires on tractor vibrations due to drawbar pull oscillation was analyzed and compared with the standard tires and special type of steel wheels with grousers. Study [64] presented a lower vibration level of spike tires than special steel wheels with grousers.…”
Section: Drawbar Pull At 100% Wheel Slipmentioning
confidence: 84%
“…The effect of spike tires on tractor vibrations due to drawbar pull oscillation was analyzed and compared with the standard tires and special type of steel wheels with grousers. Study [64] presented a lower vibration level of spike tires than special steel wheels with grousers.…”
Section: Drawbar Pull At 100% Wheel Slipmentioning
confidence: 84%
“…Therefore, soil mechanical properties affected the contact pressure below spikes and force oscillation during the wheel rotation. Analysing the drawbar pull signals by Fast Fourier transformation, Abrahám et al (2021) identified the frequency spectra typical for the spike segments. It showed the dependency of the number of spike segments on oscillation frequency.…”
Section: Resultsmentioning
confidence: 99%
“…The design of spike tyres was developed at the Slovak University of Agriculture in Nitra (Slovak Republic) and investigated by Majdan et al (2018); Abrahám, Majdan and Drlička (2019); Abrahám et al (2012). The tyres TS-02 6.5/75-14 4PR TT (Mitas, a. s., Prague, Czech Republic) were used for the special driving wheels.…”
mentioning
confidence: 99%
“…The device was developed and continuously improved at the Slovak University of Agriculture in Nitra (Slovak Republic) and allows for the setting of the active or inactive spike position. The design of this device is based on the fatigue analysis of a spike segment published in reference [26] and on a previous design version published in reference [27]. The fatigue analysis showed that the diameter of the horizontal rod connecting the left and right arms (Figure 2d,e) can be reduced from 12 mm to 10 mm.…”
Section: Spike Device With Worm Gear Unitmentioning
confidence: 99%